Analysis of speech production real-time MRI. (November 2018) - Ramanarayanan, Vikram; Tilsen, Sam; Proctor, Michael; Töger, Johannes; Goldstein, Louis; Nayak, Krishna S.; Narayanan, Shrikanth
Highlights: Presents an in-depth analysis of the state of the art in analysis of real-time MRI data of speech production. Describes with examples a unified, graphical taxonomy in which these methods can be understood and extended. Highlights a representative list of linguistic, speech and clinical applications which leverage these analysis techniques. Discusses important issues such as reproducibility of analyses along with recommendations to research practitioners. Abstract: Recent advances in real-time magnetic resonance imaging (RT-MRI) have made it possible to study the anatomy and dynamic motion of the vocal tract during speech production with great detail. The abundance of rich data on speech articulation provided by medical imaging techniques affords new opportunities for speech science, linguistics, clinical and technological research and application development, but also presents new challenges in audio–video data analysis and data modeling. We review techniques used in analysis of articulatory data acquired using RT-MRI, and assess the utility of different approaches for different types of data and research goals.